Team Reflexivity and Innovation: The Moderating Role of Team Context. (March 2015) - Schippers, Michaéla C.; West, Michael A.; Dawson, Jeremy F.
Team reflexivity, the extent to which teams collectively reflect upon and adapt their working methods and functioning, has been shown to be an important predictor of team outcomes, notably innovation. As described in the current article, the authors developed and tested a team-level contingency model of team reflexivity, work demands, and innovation. They argue that highly reflexive teams will be more innovative than teams low in reflexivity when facing a demanding work environment. A field study of 98 primary health care teams in the United Kingdom corroborated their predictions: Team reflexivity was positively related to team innovation, and team reflexivity and work demands interacted such that high levels of both predicted higher levels of team innovation. Furthermore, an interaction between team reflexivity, quality of physical work environment (PWE), and team innovation showed that poor PWE coupled with high team reflexivity was associated with higher levels of team innovation. These results are discussed in the context of the need for team reflexivity and team innovation among teams at work facing high levels of work demands.